Ameliorative Potentials of Quercetin in Some Histo-Physiological and Biochemical Parameters Against Alterations Induced Benzene Inhalation in Albino Rats - Ismail , Treefa Farouq; Abdulkareem, Saman Muhsin; Jafar, Sarwar Nawzad (Iraqi Journal of Science, 2023)
Present study investigates the protective role of quercetin in reducing benzene-induced toxicity in rats. Sixteen adult rats, weighing 200-250 g, were selected. They were divided into four groups: 1. Control group, 2. Benzene inhaled group, 3. Quercetin group and 4. Group of benzene and quercetin in combination. Biochemical, spermatological parameters, and histopathological changes in lungs were recorded. Results of aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), urea and creatinine levels in the serum of rats were higher in benzene exposed rats than in unexposed rats. Conversely, exposure to benzene led to a decrease in sperm quality compared to the unexposed rats. Histopathological examinations of the lung tissues revealed structural changes in exposed rats, including emphysema, thinning of the wall of the alveolar sac, congestion between the alveolar sacs and more elasticity in the wall of smooth muscles. The present study showed that quercetin treatment can reverse the negative effects of benzene in approximately all studied parameters and showed amelioration in the histological anomalies induced by benzene toxicity.